Gamified-Assessment For Learning Indonesian as A Foreign Language: Heuristic Evaluation Approach - Darmawansah (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Negeri Jakarta, 2020)
While the current assessment mostly repletes with paper-based or switching to online-based to see the assessment efficiency, gamified-assessment is underexplored yet. Even though the widespread of gamification phenomenon has been observed in the particular foreign language, the scarcity of game-based for assessment in learning Indonesian as foreign language forces this study to heuristically evaluate ‘travelling-like’ game. It aims to assess non-native students in higher education for learning Indonesian as a foreign language (BIPA). To this end, the study was supported by six Indonesian teachers who are currently teaching the Indonesian language in various countries or regions. The outcome of the study is thirteen heuristics which contains a set of checklist items related to an educational game framework called HEDEERS. Both the heuristics and the discussions can identify essential aspects of assessment design in both educational and game perspectives that will impact users experiences for learning the Indonesian language in a better approach